Demographic Losses due to Women’s Suicide in Lithuania 2007–2020: Social Disparities and Challenges for Mental Health Policy - Stumbrys, Daumantas; Pūras, Dainius (Socialinė teorija, empirija, politika ir praktika, 2021)
In many countries of the world, including Lithuania, suicide rates for men are several times higher than for women. Therefore, the phenomenon of men’s suicide is receiving a lot of attention in public, scientific, and political discourses. In contrast, much less attention is paid to tackling women’s suicides and women’s mental health problems. Lithuania has been among the countries with the highest suicide rates for both men and women in the world for several decades, but research on the social and demographic aspects of women’s suicide in Lithuania is lacking. This paper aims to examine the demographic losses that Lithuania suffers from women suicides and assess the socio-demographic differentiation of these losses. The empirical part of the study was based on the calculation of years of life lost methodology. The years of life lost method is acknowledged as an accurate measure for assessing the impact of specific causes of death on premature mortality. Data sources for this study were the World Health Organization, Institute of Hygiene, and Human Mortality Database. The results of our study show that the number of years of lives lost due to women’s suicide decreased statistically significantly from 376 [321; 431] in 2007 to 287 [238; 335] in 2020. In Lithuania, the total number of women suicide was the highest among the 80+ year age group, however, the number of years of life lost due to suicide was the highest among the 30-39 year age group. The change in women’s suicide rates was inconsistent and for women, the decline in demographic loss due to suicide was twice as slow as for men. Nevertheless, the number of years of lives lost due to women’s suicide was about 5 times smaller than that of men in 2020. In Lithuania, high rates of women’s suicide reflect the poor state of women’s mental health, which poses challenges to the country’s mental health policy and sustainable demographic development.